IMPROVING TEACHER LEARNING QUALITY THROUGH THE SUPERVISION OF FRIENDLY CLASSES IN "SMP NEGERI KOTA PROBOLINGGO" - Achmad Philip (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2020)
Supervision in education is known as administrative supervision and academic supervision. Academic (instructional) supervision is carried out by supervisors or principals, the aim is directed at improving the quality of learning, therefore the assessment is more qualitative directed at improving the quality of learning. Academic supervision contributes to the teaching performance of teachers so that the quality of learning produced is expected to increase.Based on the description of the results of the School Action Research (PTS) and Analysis of the results of coaching by streamlining Academic-based classroom supervision at the SMP Negeri Kota Probolinggo  Fostered School it can be concluded that through the Supervision of Friendly Classes can Improve the Quality of Teacher Learning at the SMP Negeri Kota Probolinggo  Fostered Schools. The score of the Learning Implementation Plan increased 27.9% from the first cycle with an average of 3.4 to an average of 4.4 in the second cycle, while the score for the implementation of the learning implementation increased 16.8% from the first cycle with an average of 3.7 to an average of 4.3 in the second cycle.